1993
DOI: 10.1038/bjc.1993.136
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localisation of pS2 protein in ductal carcinoma in situ and benign lesions of the breast

Abstract: Summary The expression of pS2 was examined histochemically in paraffin sections taken from biopsy material from patients diagnosed with ductal carcincoma in situ (DCIS). Often intense immunoreactivity, to an anti-pS2 monoclonal antibody, was observed in comedo, solid, cribriform and micropapillary types of DCIS, with significant positivity found in 63-67% of cases. In 15 samples analysed, we found a good correlation between pS2 expression and presence of progesterone receptor positive cells, but not with estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…However, no information is currently available in the literature regarding cytosolic PS2 levels and response to endocrine therapy for advanced disease. Irrespective of the technique used to assess PS2, as in the present study, the expression of PS2 in human primary breast tumours has shown to be correlated with that of ER or PgR Henry et al, 1989Henry et al, , 1991Skilton et al, 1989;Foekens et al, 1990Foekens et al, , 1993Schwartz et al, 1991;Cappelletti et al, 1992;Koerner et al, 1992;Predine et al, 1992;Thor et al, 1992;Gion et al, 1993;Luqmani et al, 1993b;Thompson et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…However, no information is currently available in the literature regarding cytosolic PS2 levels and response to endocrine therapy for advanced disease. Irrespective of the technique used to assess PS2, as in the present study, the expression of PS2 in human primary breast tumours has shown to be correlated with that of ER or PgR Henry et al, 1989Henry et al, , 1991Skilton et al, 1989;Foekens et al, 1990Foekens et al, , 1993Schwartz et al, 1991;Cappelletti et al, 1992;Koerner et al, 1992;Predine et al, 1992;Thor et al, 1992;Gion et al, 1993;Luqmani et al, 1993b;Thompson et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…The pS2 gene, which was originally isolated by virtue of its oestrogen-inducibility [15], has been shown to be associated predominantly with ER-positive breast cancers [9]. Although significant pS2 positivity has been reported in benign proliferative conditions of the breast [14], its positivity in PT has not been reported. We found more frequent expression of pS2 in FA than in PT regardless of the similarities in positivity for ER and PgR.…”
Section: Discussionmentioning
confidence: 98%
“…Mouse anti-pS2 antibody recognizes the estrogen-induced cytoplasmic polypeptide pS2 that is expressed in estrogen receptor positive breast cancers. 31 MCF-7-VEGF-C cell metastases in regional lymph nodes varied between those occupying only the subcapsular space to highly infiltrative lesions that destroyed normal tissue architecture (Fig. 5b-d).…”
Section: Vegf-c Induced Lymph Node Metastases In Mcf-7 Tumorsmentioning
confidence: 99%